Desenvolvimento de sistemas líquido cristalinos contendo Ac-WAhx-KTTKS para o tratamento do envelhecimento cutâneo - Guglielmi, Danila Aparecida Scatolin [UNESP] (2013)
The skin is the only organ that reflects the inevitable changes that occur in the aging process of the body. Being primarily caused by exposure to ultraviolet radiation and the chronological process. Skin aging is typically characterized by low production and destruction of collagen fibers and loss of subcutaneous fat leading to facial lines and wrinkles. The KTTKS is a peptide that stimulates collagen synthesis (type I and type III) in the skin, commonly used in cosmetic formulations for the treatment of aging skin, but due to their chemical-physical characteristics, its penetration into the skin is inefficient. To improve penetration of the skin to KTTKS reach the dermis and exercise their stimulatory effect of collagen synthesis, changes in its peptide sequence can be performed to improve their physicochemical characteristics and consequently its availability. Functional ingredients and innovative delivery systems are leading a new era of product development. The liquid crystalline systems carriers of active compounds are promising active delivery systems. Have an aim get systems loaded with hydrophilic or lipophilic active, release properties, the product stability and low toxicity. These delivery systems have as main objectives modulate the active release, aid the penetration of the skin and even administer an active ingredient one or more layers of skin, minimizing systemic involvement. The aim this study was to synthesize an analog of KTTKS, named Ac-WAhx-KTTKS, in order to improve its physicochemical properties, to obtain favorable results with its permeation into the skin and develop liquid crystalline systems for incorporation this peptide. Based on cytotoxicity and biosynthesis of collagen assays can determine the optimal concentration of the peptide Ac-WAhx-KTTKS for incorporation into formulations and obtain safe and effective systems. It was possible to obtain liquid crystalline systems for the incorporation of the peptide ...